Migration and natural fate of a coal tar creosote plume: 2. Mass balance and biodegradation indicators - King, Mark W.G.; Barker, James F.; Devlin, John F.; Butler, Barbara J. (Journal of contaminant hydrology, 1999)
A source of coal tar creosote was emplaced below the water table at CFB Borden to investigate natural attenuation processes for complex biodegradable mixtures. A mass balance indicated that ongoing transformation occurred for seven study compounds. Phenol migrated as a discrete slug plume and almost completely disappeared after 2 years, after being completely leached from the source early in the study. The m-xylene plume migrated outward to a maximum distance at approximately 2 years, and then receded back towards the source as the rate of mass flux out of the source decreased to below the overall rate of plume transformation. Carbazole showed similar behaviour, although the reversal in plume development occurred more slowly. The dibenzofuran plume remained relatively constant in extent and mass over the last 2 years of monitoring, despite constant source input over this period, providing evidence that the dibenzofuran plume was at steady state. Meanwhile, the naphthalene and 1-methylnaphthalene plumes continued to advance and increase in mass over the observation period, although at a decreasing rate. The phenanthrene plume was also subject to transformation, although measurement of the rate was less conclusive due to the higher proportion of sorbed mass for this compound. Three lines of evidence are presented to evaluate whether the observed plume mass loss was due to microbial biodegradation. Measurement of redox-sensitive parameters in the vicinity of the plume showed the types of changes that would be expected to occur due to plume biodegradation: dissolved oxygen and SO 4 2− decreased in groundwater within the plume while significant increases were noted for Fe 2+, Mn 2+ and methane. Further evidence that plume mass loss was microbially-mediated was provided by the accumulation of aromatic acids within the plume. Measurements of phospholipid fatty acids (PLFA) in aquifer material indicated that microbial biomass and turnover rate were greater within the plume than outside: also consistent with biodegradation. Study results highlight the potential for utilizing natural attenuation as a site cleanup approach for dissolved phase plumes from complex organic mixture like coal tar creosote.